The National Health Service - Great Britain. Central Office of Information. (London : His Majesty's Stationery Office, 1948)
1948 1948 1940s 38 pages REGIONAL HOSPITAL AREAS in England and Wales [map] R.H.A. Boundaries [Picture] Regional Head Offices [Picture] County Boundaries [Picture] FOURTEEN REGIONAL HOSPITAL BOARDS are responsible for the administration of the hospital and specialist services in England and Wales (with the exception of the 36 teaching hospitals, each of which has its own Board of Governors). 21/1489